Attachment in individuals with eating disorders compared to community controls: A systematic review and meta‐analysis. Issue 5 (14th March 2023) - Jewell, Tom; Apostolidou, Eleni; Sadikovic, Kevser; Tahta‐Wraith, Kirsty; Liston, Sarah; Simic, Mima; Eisler, Ivan; Fonagy, Peter; Yorke, Isabel
Abstract: Objective: Individuals with eating disorders are known to have higher rates of insecure attachment compared to community controls, but the factors underlying this finding are poorly understood. We conducted the first meta‐analysis comparing attachment in eating disorder samples compared to community controls that included quality assessment, publication bias and moderation analysis. Method: We pre‐registered our meta‐analysis (CRD42019146799) and followed PRISMA guidelines. We searched PsychINFO, Embase, Medline, CINAHL, and Scopus for publications. Attachment scores were extracted, and Cohen's d calculated for each study using a random effects model. Results: In total, 35 studies were included in the meta‐analysis and six studies were summarized in a narrative review. Eating disorder samples showed higher rates of insecure attachment compared to community controls, with a large effect size, across measurement methods and different attachment dimensions. Blinding of assessors moderated effect sizes for attachment interview studies, but no other moderators were significant. Discussion: Risk of insecure attachment is elevated in individuals with eating disorders, albeit heterogeneity is high and largely unexplained. Clinicians may need to take this into account in their work, particularly given the association between attachment insecurity and challenges to therapeutic alliance. Future studies comparing eating disorder samples with community samples should control for general psychopathology. Public Significance: Attachment is a broad concept referring to a person's thoughts, feelings and behaviors in relation to close others. This systematic review and meta‐analysis found that individuals with eating disorders are lower in attachment security than community controls, regardless of attachment construct or measurement approach. Attachment may be relevant in influencing eating disorder recovery, the development of therapeutic alliance, and potentially clinical outcomes, although more research is needed. Abstract: Apego en individuos que padecen trastornos de la conducta alimentaria en comparación con controles comunitarios: una revisión sistemática y metaanálisis. Objetivo: Se sabe que las personas que padecen trastornos de la conducta alimentaria tienen tasas más altas de apego inseguro en comparación con los controles comunitarios, pero los factores subyacentes a este hallazgo son poco conocidos. Realizamos el primer metaanálisis que comparó el apego en muestras de personas que padecen trastornos de la conducta alimentaria en comparación con controles comunitarios que incluyeron evaluación de la calidad, sesgo de publicación y análisis de moderación. Método: Se pre‐registró nuestro metaanálisis (CRD42019146799) y seguimos las guías PRISMA. Se realizaron búsquedas de publicaciones en PsychINFO, Embase, Medline, CINAHL y Scopus. Se extrajeron las puntuaciones de apego y se calculó la d de Cohen para cada estudio utilizando un modelo de efectos aleatorios. Resultados: En total, se incluyeron 35 estudios en el metaanálisis y seis estudios se resumieron en una revisión narrativa. Las muestras de personas que padecen trastornos de la conducta alimentaria mostraron tasas más altas de apego inseguro en comparación con los controles comunitarios, con un gran tamaño del efecto, a través de métodos de medición y diferentes dimensiones de apego. El cegamiento de los evaluadores moderó los tamaños del efecto para los estudios de entrevistas de apego, pero ningún otro moderador fue significativo. Discusión: El riesgo de apego inseguro es elevado en individuos que padecen trastornos de la conducta alimentaria, aunque la heterogeneidad es alta y en gran medida inexplicable. Los clínicos pueden necesitar tener esto en cuenta en su trabajo, particularmente dada la asociación entre la inseguridad del apego y los desafíos a la alianza terapéutica. Los estudios futuros que comparen muestras de individuos que padecen trastornos de la conducta alimentaria con controles comunitarios deben controlar la psicopatología general.